Isolation and Characterization of Bacillus velezensis Strain P2-1 for Biocontrol of Apple Postharvest Decay Caused by Botryosphaeria dothidea - Yuan, Hongbo; Shi, Bingke; Wang, Li; Huang, Tianxiang; Zhou, Zengqiang; Hou, Hui; Tu, Hongtao (Frontiers in Microbiology, 2022)
Botryosphaeria dothidea causes apple ring rot, which is among the most prevalent postharvest diseases of apples and causes significant economic loss during storage. In this study, we investigated the biocontrol activity and possible mechanism of Bacillus velezensis strain P2-1 isolated from apple branches against B. dothidea in postharvest apple fruit. The results showed strain P2-1, one of the 80 different endophytic bacterial strains from apple branches, exhibited strong inhibitory effects against B. dothidea growth and resulted in hyphal deformity. B. velezensis P2-1 treatment significantly reduced the ring rot caused by B. dothidea. Additionally, the supernatant of strain P2-1 exhibited antifungal activity against B. dothidea. Re-isolation assay indicated the capability of strain P2-1 to colonize and survive in apple fruit. PCR and qRT-PCR assays revealed that strain P2-1 harbored the gene clusters required for biosynthesis of antifungal lipopeptides and polyketides. Strain P2-1 treatment significantly enhanced the expression levels of pathogenesis-related genes (MdPR1 and MdPR5) but did not significantly affect apple fruit qualities (measured in fruit firmness, titratable acid, ascorbic acid, and soluble sugar). Thus, our results suggest that B. velezensis strain P2-1 is a biocontrol agent against B. dothidea-induced apple postharvest decay. It acts partially by inhibiting mycelial growth of B. dothidea, secreting antifungal substances, and inducing apple defense responses.